Factors Associated with Diarrheal Dehydration in Toddlers at Kalijudan Health Center Work Area - Meivi Yusinta Christy (Universitas Airlangga, 2014)
ABSTRACT One of common health problem among toddlers in Indonesia is diarrhea. Diarrhea is a disease that has risk to cause death. The main causes of death in diarrhea is dehydration by the loss of fluids and electrolytes through feces. Based on monthly reports of diarrhea at Kalijudan Health Center (Indonesian: Puskesmas Kalijudan) in 2013, there were some toddlers aged 1-4 years old that suffered dehydration due to diarrhea. This research aimed to analyze the relationship between maternal characteristics and knowledge and the incidence of toddler dehydration due to diarrhea at Kalijudan Health Center, Surabaya. This research was an analytic observational research with case-control design. Subjects of the research were drawn from the population using simple random sampling. Number of samples obtained was 30 individuals for case group and another 30 for control group. The independent variables were the characteristics of the toddler's mother (including age, education, work statu, family income) and knowledge of the toddler's mother. Primary data were collected using questionnaires. Analysis of the data was done using Chi Square statistical test. The results of bivariate analysis, it was found that the variables associated with the incidence of diarrheal dehydration among toddlers were mother's work status (p = 0.010), and knowledge of the toddler's mother (p = 0.002). There were no relationship among age of toddlers' mother (p = 0.779), mother's education (p = 0.797), and family income (p = 0.430). The conclusion that could be drawn was the work status and knowledge of the toddler's mother was significantly associated with the incidence of diarrheal dehydration in toddlers. There is needs of education or health promotion for mothers concerning to proper management of diarrhea for toddlers using prevention of diarrhea through seven interventions. Keywords: characteristics, knowledge, mother's toddler, diarrhea dehydration, toddler